(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Rozwody są prawdopodobnie najliczniejszą kategorią spraw z zakresu prawa rodzinnego występującą w polskich sądach. Autor artykułu przedstawia stosunek wzajemny dwóch przesłanek rozwodowych obowiązujących w polskim ustawodawstwie, mianowicie winy i zasad współżycia społecznego. Rozważania swoje opiera na regulacjach Kodeksu Rodzinnego i Opiekuńczego z 1964 r. oraz bogatym orzecznictwie sądów, w szczególności Sądu Najwyższego. Divorces are probably the most numerous category of family law cases occurring in Polish courts. The author of this article presents the reciprocal relationship of the two grounds for divorce in force in Polish legislation, namely guilt and principles of social co-existence. He bases his considerations on the regulations of the 1964 Family and Guardianship Code and a wealth of case law from the courts, in particular the Supreme Court.